Gambaran penanganan penyakit kronis: program rujuk balik penyakit jantung koroner pada dokter keluarga di Kota Manado - Naamin, Jihan; Kuhon, Frelly Valentino; Ottay, Ronald I. (Jurnal Kedokteran Komunitas dan Tropik, 2022)
Introduction: Chronic disease is one of the health problems in Indonesia which continues to increase and has not been successfully reduced. Coronary heart disease (CHD) is a chronic disease which has been a major cause of death and global burden of disease. The prevalence of CHD in North Sulawesi is 1.8%, exceeding the national prevalence, making North Sulawesi the fourth highest province in Indonesia. The management of CHD aims to prevent recurrent coronary events and complications by modifying risk factors. Holistic approach is needed to identify the risk factors that cause CHD. Family medicine is a medical specialty that provides health care with a holistic approach at first-level health facilities. Program Rujuk Balik (PRB), as one of the leading programs, is optimized to improve the quality of health services for the participants of BPJS Kesehatan and to facilitate access to health services for participants who have chronic diseases. The catastrophic costs can be minimized through holistic management of CHD by family physicians maximizing the function of PRB. Objective: To determine the overview of the management of PRB participants with CHD by family physicians in Manado City. Methods: This research is a descriptive study with a cross-sectional design. Results: It was found that all respondents were in the good category at managing the participants of PRB with CHD (100%). Conclusion: The management of the participants of PRB with CHD by family physicians in Manado City has been well. Keywords: program rujuk balik, coronary heart disease, family physicians.